Negative Political Advertising: It’s Impact on Voters - Ernest Cyril, de Run; Jee, Teck-Weng; Lau, Wee Ming (Asian Journal of Business Research, 2013)
This study looks at a one of the many use of a direct negative advertisement in Malaysian politics. Negative advertising has been constantly used by political parties in Malaysia. This paper looks specifically at one of such advertisements and its effect on voters where it was specifically aimed at (Batang Ai, Sarawak). The study measures attitude towards the advertisement, advertisement likeability, advertisement believability, positive emotional quotient towards the advertisement and its affect on actual behavior. Response was obtained from Batang Ai voters and divided into two groups, Barisan Nasional and non-Barisan Nasional voters. A total of 150 respondents were used in this study and the data were analyzed using descriptive analysis, Independent Sample t-test, Correlation and Regression. The findings indicate significant difference between Barisan Nasional and non-Barisan Nasional for all variables except for attitude towards the advertisement. It also shows that advertising believability is the only variable that impacts actual behavior.